Rick Warren, purpose driven en die 40 dae doelgerigte lewe veldtog - Ungerer, Andre (HTS teologiese studies, 2007)
Rick Warren, purpose driven and the 40 days of purpose campaign More than 532 churches/congregations in South-Africa have already purchased “The purpose driven campaign kit” and completed the 40 days campaign or are planning to do so. The name Rick Warren is synonymous with “Purpose driven” and the popularity of his work as well as his influence in this country, justifie a study of this nature. This study wants to determine the effect of Rick Warren’s 40 days of purpose in the circuit of Klerksdorp of the Nederduitsch Hervormde Kerk van Afrika. Warren provides five purposes for a believer in the church in his book, A purpose driven life, which according to him is the church’s purpose of existence. The hypothesis of this study is that the 40 days of purpose is an excellent project for congregations to discover their purpose of existence, while it also strengthens the process of building the local congregation. Eight congregations participated in the research project.